Аналіз доцільності впровадження технології «активний будинок» в кліматичних умовах північно-східної України - Данилова, Олена Анатоліївна; Золотарьов, Денис Олегович; Лисенко, Людмила Іванівна (Національний технічний університет "Харківський політехнічний інститут", 2019)
«Активний будинок» це будинок з позитивним енергобалансом, важливою особливістю якого є власне виробництво електроенергії за рахунок відновлюваних джерел, при цьому кількість виробленої енергії перевищує власні потреби, що дозволяє поставляти надлишок у локальну мережу. В роботі досліджено можливість і доцільність впровадження цієї технології на прикладі об’єднання 10 «активних» будинків в Харківської області. Розглянуто три групи мешканців, що відрізняються характером електроспоживання, можливість покриття усередненого добового навантаження об’єднання «активних» будинків за рахунок 315 ФЕМ PV-260M-260 Вт, 4 ВЕУ СВ-6.7/2000-7 кВт і 16 акумуляторних батарей Tesla Powerwall 2 AC. Проаналізовано заходи що до покриття споживання об’єднання «активних» будинків у випадку несприятливих погодних умов. Оцінено економічну ефективність інвестицій в такий проект.

“Active house” is a house with positive energy balance (“energy-plus house”) the important feature of which consists in self-contained electricity production via renewable energy sources, the amount of electricity generated exceeding the demand. It allows supplying the electricity surplus to local grids. The paper considers a feasibility and expediency of implementing the considered technology in Northeastern Ukraine by an example of a ten-“active”-house estate in Kharkiv region. The houses are grouped in three types according to the electricity consumption charts depending on the house dwellers behavior. The average electricity demand versus electricity produced by 21 PV 260 W modules and a 4 kW wind mill has been analyzed for various meteorological conditions to show the necessity of uniting the individual power supply systems into a common grid, which results in smoothening the load curve, with an additional common solar and wind farm and an accumulator bank to cover the load in case of unfavorable weather. The operation of the renewable energy sources and the battery system is controlled by a smart grid to rationally employ the available capacity and distribute electricity generated among the consumers. The payback period is assessed to approach 12 years with allowance for electricity bill rise with time and electricity surplus selling to the grids by feed-in tariffs.
Analysis of «active house» technology implementation expediency under climatologic conditions in northeastern Ukraine
Keywords: електроспоживання; відновлювані джерела енергії; electricity consumption; renewable energy sources